Integrasi Ekoteologi dalam Praktik Penyuluhan Agama Islam, Studi Peran Penyuluh sebagai Agen Dakwah Berkelanjutan - Nurolin Nurolin; Dian Tias Aorta (Lembaga Yasin AlSys, 2026)
Although the relationship between religion and the environment has been widely studied, research specifically discussing the integration of ecotheology into Islamic religious outreach practices and the role of religious outreach officers as agents of sustainable da'wah at the community level remains limited. This study aimed to analyze the integration of ecotheological values into Islamic religious outreach and to examine the role of religious outreach officers as agents of sustainable da'wah in the KUA Pringkuku area. This study used a qualitative approach with a case study design, involving 15 participants selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and then analyzed using thematic analysis. The results showed that ecotheological values had begun to be integrated into outreach materials, although they were not yet systematic and still depended on the initiative of religious outreach officers. The outreach method was still dominated by lectures but had begun to develop toward a more dialogical and contextual approach. The role of religious outreach officers as agents of sustainable da'wah was evident in efforts to encourage environmental awareness among the community, although its implementation was not yet consistent. Community responses tended to be positive but still showed variation in the understanding and application of ecological values. The conclusion of this study emphasizes the importance of systematically integrating ecotheology into Islamic religious outreach and the need to develop more participatory and sustainable da'wah strategies. These findings contribute to the development of Islamic ecotheology and transformative da'wah studies, while also providing practical implications for KUA and religious outreach officers in designing outreach programs that are responsive to environmental issues at the local level.